2010
DOI: 10.1177/0022219409355478
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Morphological Awareness in Reading Comprehension Among Typical and Learning Disabled Native Arabic Speakers

Abstract: This work examines the role of morphological awareness in contrast to phonological processing in reading comprehension amongst two groups of native Arabic children: a group with learning disabilities (LD) and a mainstream group who were matched to the LD group in age or reading level. Measures of reading comprehension fluency, phonological skills, and morphological ability were given to both groups in addition to tests of nonverbal ability. For the mainstream children, unique variability in comprehension was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 58 publications
2
31
0
2
Order By: Relevance
“…The obtained results stress the multi-componential aspects of reading in Arabic, requiring a broader perspective, transcending phonology while considering other precursors of reading, such as morphological awareness (e.g. Mahfoudhi, Elbeheri, Al-Rashidi, & Everatt, 2010;Makhoul & Ibrahim, 2012;Mutlak, 2010). In the current study, positive significant correlation was found in the HG group between morphology and all reading measures with listening comprehension.…”
Section: Discussionsupporting
confidence: 52%
“…The obtained results stress the multi-componential aspects of reading in Arabic, requiring a broader perspective, transcending phonology while considering other precursors of reading, such as morphological awareness (e.g. Mahfoudhi, Elbeheri, Al-Rashidi, & Everatt, 2010;Makhoul & Ibrahim, 2012;Mutlak, 2010). In the current study, positive significant correlation was found in the HG group between morphology and all reading measures with listening comprehension.…”
Section: Discussionsupporting
confidence: 52%
“…In another study conducted in Arabic, for average readers, unique variability in reading comprehension was predicted by the morphological measures beyond measures of phonological skills and general nonverbal ability. In contrast, for the RD readers, variability in comprehension was not predicted by morphological ability even though they performed as well as their typically developing peers in the morphology task (Mahfoudhi, Elbeheri, Elbeheri, & Everatt 2010). Taken together, research suggests that important differences exist between reading comprehension predictors among RD and NRD readers.…”
Section: Predicting Reading Comprehension Among Rd and Nrdmentioning
confidence: 67%
“…The focus of Allaith and Joshi's paper is the sounds (phonemic inventory) within the two languages and, therefore, there is a good introduction to these differences in their paper. However, there are other factors that are worthy of consideration, such as the focus on morphological features of the Arabic language which extends to the Arabic orthography, despite the potentially high level of symbol-sound correspondence between orthography and language (see review in Mahfoudhi, Elbeheri, Al-Rashidi, & Everatt, 2010). Further research is needed to determine whether morphological awareness is more important in Arabic literacy learning compared to other languages, such as English, as well as its role in both typical development and those presenting evidence of specific difficulties in literacy acquisition.…”
Section: Language Factorsmentioning
confidence: 99%